Science communication on the internet : old genres meet new genres - Luzón, María José, 1969-; Pérez-Llantada, Carmen (Pragmatics & beyond, 2019)
"This book examines the expanding world of genres on the Internet to understand issues of science communication today. The book explores how some traditional print genres have become digital, how some genres have evolved into new digital hybrids, and how and why new genres have emerged and are emerging in response to new rhetorical exigences and communicative demands. Because social actions are in constant change and, ensuing from this, genres evolve faster than ever, it is important to gain insight into the interrelations between old genres and new genres and the processes underpinning the construction of new genre sets, chains and assemblages for communicating scientific research to both expert and diversified audiences. In examining scientific genres on the Internet this book seeks to illustrate the increasing diversification of genre ecologies and their underlying social, disciplinary and individual agendas"--